2017
DOI: 10.1038/hr.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the association of cardiorespiratory fitness and arterial stiffness in children and adolescents

Abstract: The relationship between cardiorespiratory fitness and arterial compliance in children and adolescents remains controversial. The aim of this study was to assess this association with a quantitative approach. A total of 646 healthy children and adolescents (316 females, age 13.9±2.1 years) were cross-sectionally investigated in seven school settings in and around Munich for their cardiorespiratory fitness and demographic, anthropometric and hemodynamic parameters. Surrogates of arterial stiffness, such as puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…As far as cardiorespiratory fitness parameters are concerned, we could not demonstrate that VO 2max was associated with stiffness parameters. Compared to the computed VO 2max values, the amount of shuttle run rounds were positively associated with PWV and CSBP in the whole study group, The results share similarities with Meyer et al who studied surrogates of arterial stiffness in n = 646 German adolescents (age 13.9 ± 2.1 years) with the Mobil-O-Graph (9). In their cohort PWV was also positively associated with CRF, whereas CSBP showed no association.…”
Section: Cardiorespiratory Fitness and Arterial Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…As far as cardiorespiratory fitness parameters are concerned, we could not demonstrate that VO 2max was associated with stiffness parameters. Compared to the computed VO 2max values, the amount of shuttle run rounds were positively associated with PWV and CSBP in the whole study group, The results share similarities with Meyer et al who studied surrogates of arterial stiffness in n = 646 German adolescents (age 13.9 ± 2.1 years) with the Mobil-O-Graph (9). In their cohort PWV was also positively associated with CRF, whereas CSBP showed no association.…”
Section: Cardiorespiratory Fitness and Arterial Propertiessupporting
confidence: 81%
“…Studies in children (9,10) have examined the relationship between cardiorespiratory fitness (CRF) and arterial distensibility. Besides the positive effects of healthy CRF (11), literature also demonstrated that resistance training may be effective for improving vascular health in adults and adolescents (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure and arterial stiffness were automatically measured on the left upper arm with the oscillometric cuff-based Mobil-O-Graph device in a supine position after 5 min rest. Cuffs were chosen according to the circumference of the left upper arm (Elmenhorst et al, 2014; Meyer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Two studies investigated the associations between carotid distensibility and CRF; only Ried-Larsen et al (37) reported a positive relationship (36,37). Two of the three studies documented a positive association between carotid arterial compliance and CRF (21,37,48), while aortic AI@75 (the AI at a standardized heart rate of 75 beats per minute) was inversely associated with CRF (47).…”
Section: Vascular Functionmentioning
confidence: 99%